Maternal and Newborn Outcomes Among Women With Schizophrenia. Issue 2 (June 2015) - Vigod, S.N.; Kurdyak, P.A.; Dennis, C.L.; Gruneir, A.; Newman, A.; Seeman, M.V.; Rochon, P.A.; Anderson, G.M.; Grigoriadis, S.; Ray, J.G.
<x xml:space="preserve">Abstract</x> (BJOG. 2014;121(5):566–574)